Stability of Palatal Rugae after Rapid Maxillary Expansion (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Palatal rugae or plicae palatine are uneven ridges made of connective tissue situatedbeneath the incisive papilla. DNA analysis, finger prints analysis, are the most common techniques usedfor establishing person’s identity but in situation where using these techniques are difficult palatal rugaecan be used as a second source of identification. However, some habits like prolonged thumb sucking andorthodontic treatment for long duration could affect the rugae pattern. Hence, this study aims to evaluate thechanges in transverse dimensions of palatal rugae in subjects treated with rapid maxillary expansionMaterial and Methods: The palatal rugae patterns were measured and compared to evaluate the morphometricchanges between pre-treatment cast (30 Pre-RME) and its post-treatment (30 Post-RME) counterpart. Allpre-and post-expansion dental casts were traced and the intermedial and interlateral dimensions of first,second and third rugae were measured. The statistical analysis was done using paired t test.Conclusion: The medial aspect of first primary rugae can be considered as a stable reference landmarkwhile the lateral and medial aspects of the 2nd and 3rd rugae are liable to changes in transverse dimension.Hence, for forensic identification the stability of palatal rugae in patients who had undergone rapid maxillaryexpansion still remains questionable
Keywords: Rapid Maxillary Expansion, Palatal rugae, Transverse dimension